Republic of Mauritius : Accounting and Auditing - World Bank (Washington DC, 2013)
This report is part of the Bank and International Monetary Fund joint initiative on Reports on the Observance of Standards and Codes (ROSC). The ROSC- Accounting & Auditing review process involved an assessment of local accounting and auditing standards, and actual practices and analysis of effectiveness of the mechanisms for ensuring compliance with the formal standards. The review used a diagnostic template developed by the Bank to facilitate a self-assessment by a National Steering Committee established by the Minister of Economic Development, Financial Services, and Corporate Affairs. The self-assessment results, complemented by the findings of a due diligence exercise conducted by Bank staff, were used in preparing this report. The policy recommendations of this report specifically focus on strengthening the monitoring and enforcement arrangements through a proposed Financial Reporting Council. This body will develop, and disseminate guidelines on international accounting and auditing standards, monitor compliance with financial reporting requirements, conduct practice review of the auditors and audit firms, and enforce actions against infractions. For expediting the implementation of IAS and ISA, there is a need for bolstering professional education and training arrangements.